The Student's Style in Learning English at Islamic Senior High School - Didik Santoso; Muammar Suharso; Siregar, Fatimah Azzahra; Silvi Angelika; Cut Ria Manisha (PT. Kreasi Karya Majakata, 2024)
In this era, Learning is a fundamental aspect that must be taken into consideration. An important step in the teaching process is developing the teacher's strategy and the student's learning style. The purpose of this study is to investigate the types of learning styles that students use when learning English. This study employs a qualitative research design. This study employs a case study methodology. This study was conducted from May 27, 2024, to June 1, 2024, at SMAS Al Hijrah II, located on Jl. Lau Dendang in Deli Serdang. Data is taken from the XI-grade students. Approximately eight students were sampled using purposive sampling. Wawancara and observation are used in data collection to gather data. The research findings indicate that there are four types of learning styles used by researchers: visual, auditory, read-write, and kinesthetic (VARK)